PROFESIONALISME GURU DALAM UPAYA PEMBENTUKAN PESERTA DIDIK YANG BERKUALITAS - Halid Hanafi (IAI DDI Mangkoso, 2024)
Professional teachers are teachers who are experts in their field, able to apply their knowledge, have a good attitude and are able to make students become qualified. This research uses a library method by conducting an in-depth and systematic study of various relevant literature sources so that appropriate answers are obtained regarding the problems studied. The existence of professional teachers in a school plays a very important role in developing the quality of students because professional teachers are able to carry out their duties optimally, are experts in the scientific field they are involved in, are able to manage learning methods well, are able to manage various learning media and are able to collaborate with various parties in an effort to create quality students. This condition can be realized because professional teachers have followed the educational process according to their professional field, continue to develop their scientific field, have a commitment to change, are able to see problems far into the future in responding to the challenges faced in managing educational activities and carry out teaching activities with a full sense of responsibility.